Adverse Childhood Experiences and Adult Distress : The Role of Type and Timing of Exposure - Lahdenkari, Pinja (My University, 2023)
Adverse childhood experiences (ACEs), such as different forms of abuse and neglect, are linked to different psychopathologies, including depression and anxiety. It is widely known that the risk for negative health outcomes increases with the number of ACEs, but more studies are needed to examine the role of type and timing. The present study examined the connection between ACEs and adulthood depression and anxiety and sought to find out whether there is a difference in adulthood distress based on the type and the timing of exposure to ACEs. The sample (N=4966) comprised of mothers and fathers recruited for the ongoing FinnBrain Cohort Study, which this study is a part of. The data were collected using self-report questionnaires, including TADS, EPDS and SCL-90. The ACE types in this study were emotional and physical abuse and neglect, as well as sexual abuse. According to the timing of exposure, three time periods were defined: ACEs occurring prior to age 6, between ages 7 and 12 or between ages 13 and 18. The Relative Weight Analysis (RWA) was conducted to examine the predictive role of ACE type and timing of exposure. ACEs were associated with increased symptoms of depression and anxiety, and ACEs during adolescence showed to have the most significant impact. Emotional abuse played a central role in predicting paternal anxiety and depression as well as maternal anxiety. Emotional neglect had the most significant impact on maternal depression. The predictive role of other ACE types was significantly lower.
Keywords: adverse childhood experiences (ACEs), ACE type, timing of exposure, distress, depression, anxiety